Factors influencing customers to choose Bank Rakyat Islamic credit card / Siti Nur'ain Ismail Yatim - Ismail Yatim, Siti Nur'ain (Faculty of Business and Management, 2019)
Islamic credit card provides various facility such as credit facility or advanced payment. This research to study the factors influencing customers to choose the Bank Rakyat Islamic Credit Card by using Innovation Diffusion Theory (ID T) which IDT consist of relative advantage, compatibility, complexity, trialability and observability. This research is specifically focus on the Bank Rakyat Islamic credit card's customers in Bank Rakyat, Head Quarter (HQ). A descriptive study was conducted to 141 customers of Bank Rakyat. Seven section of questionnaire was distributed to the customer relating the Innovation Diffusion Theory and intention of use Bank Rakyat Islamic Credit Card. The study was found that relative advantage, compatibility and observability have significant relationship with the usage of Bank Rakyat Islamic Credit Card. The study is able to determine the factors influencing customers to choose the Bank Rakyat Islamic Credit Card despite the limitation when the customer is hardly to cooperate to respond this survey.